What happens to thyroid function in long‐term type 1 diabetes? A Winchester cohort study. (May 2015) - Brooks, AP; Barbour, H; Li Voon Chong, JSW; Kibble, S; Schapira, D; White, G; Williams, E
Abstract In a cross‐sectional analysis of 655 people with type 1 diabetes of a wide age range and duration of diabetes up to 50 years, the most common form of thyroid dysfunction was treated clinical hypothyroidism (under‐activity) in 69 of 313 females (22%) and 26 of 342 males (7.6%). Only four patients (two of each sex) had episodes of thyroid over‐activity. Serum thyroid stimulating hormone (TSH mU/L) in 493 patients (208 females and 285 males) who maintained normal thyroid function was remarkably steady. After 10 years' duration of type 1 diabetes the prevalence of treated clinical hypothyroidism in females increased from 1 in 6 for 10–29.9 years' duration up to 1 in 3 for over 30 years, and respectively from 1 in 10 to 1 in 6 in males. Thyroid dysfunction, usually hypothyroidism, should be screened for annually using a serum TSH assay in all type 1 diabetes patients after 10 years' duration. In the first 10 years of type 1 diabetes thyroid dysfunction is rarer, but more variable, and must not be misdiagnosed because of its possible more severe consequences. Five of nine females who were hypothyroid were so at diagnosis of their diabetes; the other four became so in the first 12–24 months, and two had thyroid over‐activity (one recurrent). Three males were already hypothyroid when diabetes was diagnosed and two developed over‐activity. New cases of type 1 diabetes should have their thyroid function assessed clinically with thyroid hormone levels, serum TSH and antithyroid antibodies, say six‐monthly, for the first three years after diagnosis and on suspicion at any time thereafter. Copyright © 2015 John Wiley & Sons.